The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.jasms.2008.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase reactivity of ruthenium carbonyl cluster anions

Abstract: Partially-ligated anionic ruthenium carbonyl clusters react with alkenes, arenes, and alkanes in the gas phase; the products undergo extensive C-H activation and lose dihydrogen and carbon monoxide under collision-induced dissociation conditions. Triethylsilane and phenylsilane are also reactive towards the unsaturated clusters, and oxygen was shown to rapidly break down the cluster core by oxidative cleavage of the metal-metal bonds. These qualitative gas-phase reactivity studies were conducted using an easil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…The corresponding cluster k values of the fragment should be on the increase. Very interesting extensive work on the metal carbonyls that involves stripping off the CO ligands has been done by several research groups (Butcher, et al, 2002(Butcher, et al, , 2003Crawford, et al, 2006;Critchley, et al, 1999;Dyson, et al, 2001;Henderson, et al, 1998Henderson, et al, , 2009 Table 7). Although the series and the skeletal numbers predict that each of the Re skeletal atoms except one should have a hydrogen atom, the structural determination indicates all the hydrogen atoms are bridging (Miessler, et al, 2014) as observed in borane clusters.…”
Section: Limits Of the Carbonyl Cluster Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding cluster k values of the fragment should be on the increase. Very interesting extensive work on the metal carbonyls that involves stripping off the CO ligands has been done by several research groups (Butcher, et al, 2002(Butcher, et al, , 2003Crawford, et al, 2006;Critchley, et al, 1999;Dyson, et al, 2001;Henderson, et al, 1998Henderson, et al, , 2009 Table 7). Although the series and the skeletal numbers predict that each of the Re skeletal atoms except one should have a hydrogen atom, the structural determination indicates all the hydrogen atoms are bridging (Miessler, et al, 2014) as observed in borane clusters.…”
Section: Limits Of the Carbonyl Cluster Seriesmentioning
confidence: 99%
“…These opposing processes are reflected in Tables 7 and 8. The removal of CO ligands from transition metal carbonyl clusters has been an intense field of research (Critchley, et al, 1999, Douglas, et al, 2001, Butcher, et al, 2002, 2003, Crawford, et al, 2006, Henderson, et al, 2009). The silicon clusters Si n (n=4-10) were theoretically studied (Slee, et al, 1989) (Hughes, et al, 2000).…”
Section: Capping and De-capping Seriesmentioning
confidence: 99%
“…For a example,Rh 6 (CO) 16 [E = 6X18 = 108, V = 6X9+16X2 = 86, k = ½ (E-V) = ½ (108-86) = 11, M-6-11-86). By moving down the M-6 column reaching M-6-11-86,then moving across the row it is found that the cluster belongs to the closo (C) series M-6-11-86-C(14n+2) with an octahedral geometry 8 .…”
Section: Categorizing a Cluster With The Cluster Tablementioning
confidence: 99%
“…However, studies by McIndoe et al [42] demonstrated that chemically synthesized atomically precise metal clusters could be used as precursors of naked metal clusters. Similarly, reactivity studies of partially ligated gas-phase metal clusters can be performed using chemically made, atomically precise clusters as a source, and easily installed and inexpensive modifications to electrospray ionization mass spectrometers [43]. Such studies demonstrate that cluster reactivity depends not only on the number of metal atoms per cluster core, but also on the number of coordinated ligands, highlighting how sensitive the electronic properties of ultrasmall particles are to modifying interactions [44,45].…”
Section: Size Effects -Setting the Scenementioning
confidence: 99%
“…Pt cubes were 19 times more active than cuboctahedra, which, in turn, were 27 times more active than octahedral particles! However, rather than shape effect, these differences were attributed to variable Ag content (43,378, and 326 ppm Ag in the cubes, cuboctahedra and octahedra, respectively), as Ag was known to lower the Pt activity in alkene hydrogenation. When the reactivity of Ag-free TTAB-stabilized Pt cubes and cuboctahedra was studied later in benzene hydrogenation [245], clear particle shape effects became apparent [247].…”
Section: Shape Effectsmentioning
confidence: 99%